2022
DOI: 10.1093/cz/zoac012
|View full text |Cite
|
Sign up to set email alerts
|

Two lineages of bivalve transmissible neoplasia affect the blue musselMytilus trossulusGould in the subarctic Sea of Okhotsk

Abstract: There are increasing findings of the bivalve transmissible neoplasia derived from the Pacific mussel Mytilus trossulus (MtrBTN) in populations of different Mytilus species worldwide. The Subarctic is an area where this disease has not yet been sought despite the fact that Mytilus spp. are widespread there, and M. trossulus itself is a boreal species. We used flow cytometry of the hemolymph, hemocytology and histology to diagnose disseminated neoplasia in a sample of M. trossulus from Magadan in the subarctic S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
45
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(51 citation statements)
references
References 40 publications
6
45
0
Order By: Relevance
“…mussels are affected by two BTN lineages known as MtrBTN1 and MtrBTN2 that originate from two different M. trossulus founder hosts. MtrBTN2 is distributed worldwide and has crossed the species barrier several times to infect four Mytilus species: M. trossulus in East Asia [12,13], M. chilensis in South America [9], and M. edulis and M. galloprovincialis in Europe [9,14]. The oldest MtrBTN2 sample is 14 years old.…”
Section: Introductionmentioning
confidence: 99%
“…mussels are affected by two BTN lineages known as MtrBTN1 and MtrBTN2 that originate from two different M. trossulus founder hosts. MtrBTN2 is distributed worldwide and has crossed the species barrier several times to infect four Mytilus species: M. trossulus in East Asia [12,13], M. chilensis in South America [9], and M. edulis and M. galloprovincialis in Europe [9,14]. The oldest MtrBTN2 sample is 14 years old.…”
Section: Introductionmentioning
confidence: 99%
“…The only MtrBTN2 found in the Kola Bay bore the mtDNA haplotype nearly identical to a common Northwest Pacific one and noticeably different from the haplotypes of this lineage elsewhere, in particular, in Western Europe (Figure 4). In terms of cell ploidy, MtrBTN2 in the Kola Bay (ploidy 5n) was also similar to that in the Northwest Pacific (range 4.3-5.8n) but not in Western Europe (8.4-11.4n) (Figure 3; Burioli et al, 2019;Skazina et al, 2022).…”
Section: Discussionmentioning
confidence: 65%
“…In all the following analyses, the procedures were the same as in our previous studies (Skazina et al, 2021(Skazina et al, , 2022, unless indicated otherwise.…”
Section: Sample Collection and Preprocessingmentioning
confidence: 99%
See 2 more Smart Citations